Repair pathways for radiation DNA damage under normoxic and hypoxic conditions: Assessment with a panel of repair-deficient human TK6 cells. (25th September 2021) - Tsuda, Masataka; Shimizu, Naoto; Tomikawa, Hinako; Morozumi, Ryosuke; Ide, Hiroshi
Abstract: Various types of DNA lesions are produced when cells are exposed to ionizing radiation (IR). The type and yield of IR-induced DNA damage is influenced by the oxygen concentration. Thus, different DNA repair mechanisms may be involved in the response of normoxic and hypoxic cells to irradiation with IR. However, differences between the repair mechanisms of IR-induced DNA damage under normoxic versus hypoxic conditions have not been clarified. Elucidating the relative contribution of individual repair factors to cell survival would give insight into the repair mechanisms operating in irradiated normoxic and hypoxic cells. In the present study, we used a panel of repair-deficient human TK6 cell lines that covered seven repair pathways. Cells were irradiated with X-rays under normoxic and hypoxic conditions, and the sensitivities of each mutant relative to the wild-type (i.e. relative sensitivity) were determined for normoxic and hypoxic conditions. The sensitivity of cells varied depending on the type of repair defects. However, for each repair mutant, the relative sensitivity under normoxic conditions was comparable to that under hypoxic conditions. This result indicates that the relative contribution of individual repair pathways to cell survival is comparable in normoxic and hypoxic cells, although the spectrum of IR-induced DNA damage in hypoxic cells differs from that of normoxic cells.